2011
DOI: 10.1103/physrevc.83.014320
|View full text |Cite
|
Sign up to set email alerts
|

Shell-model study for neutron-richsd-shell nuclei

Abstract: The microscopic structure of neutron-rich sd-shell nuclei is investigated by using the spherical-shell model in the sd-pf valence space with the extended pairing plus quadrupole-quadrupole forces accompanied by the monopole interaction (EPQQM). The calculation reproduces systematically the known energy levels for even-even and odd-mass nuclei including the recent data for 43 S, 46 S, and 47 Ar. In particular, the erosion of the N = 28 shell closure in 42 Si can be explained. Our EPQQM results are compared with… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
61
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(64 citation statements)
references
References 42 publications
(89 reference statements)
2
61
1
Order By: Relevance
“…It has been demonstrated that despite of its simplicity, this EPQQM model works surprisingly well for different mass regions, for example, the proton-rich p f shell [10] and the p f 5/2 g 9/2 shell [11], the neutron-rich f pg shell [12], and the sd-p f shell region [13]. It has also been successfully applied to the neutron-rich nuclei around 132 Sn [14,15].…”
mentioning
confidence: 99%
“…It has been demonstrated that despite of its simplicity, this EPQQM model works surprisingly well for different mass regions, for example, the proton-rich p f shell [10] and the p f 5/2 g 9/2 shell [11], the neutron-rich f pg shell [12], and the sd-p f shell region [13]. It has also been successfully applied to the neutron-rich nuclei around 132 Sn [14,15].…”
mentioning
confidence: 99%
“…The erosion of the shell gap and the migration of neutron magic numbers such as N = 8 [1] and 20 [2] far from stability have been important and fascinating subjects in nuclear structure physics [3]. The N = 28 shell closure in neutron-rich Si and S isotopes has received considerable experimental [4][5][6][7][8][9][10][11][12][13] and theoretical attention [14][15][16][17][18][19][20][21][22][23]. Experimental data [5,6,[8][9][10][11] indicate gradual quenching of the N = 28 shell gap toward neutron-rich isotones and the onset of deformation in N ≈ 28 S and Si isotopes.…”
mentioning
confidence: 99%
“…The nuclear valence-space shell model is one of the work horses in nuclear structure theory. It is very successful for the description of spectra and spectroscopic observables over a large range of nuclei and plays an important role in guiding and interpreting experiments from stable to exotic nuclei [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17]. Two critical aspects in the application of the shell model (SM) are the construction of the effective valence-space interaction as well as corresponding effective operators and the solution of the eigenvalue problem in the model space of the valence nucleons.…”
mentioning
confidence: 99%